The Influence of Lifestyle, Price and Service Quality on Purchasing Decisions in Modern Coffee Shops (Case Study of Students in Malang City) - Utomo, Heru; Sudjanarti, Dwi; Wardani, Rr. Tri Istining; Khabibah, Umi (Transpublika Publisher, 2024)
This study aims to investigate how lifestyle, price, and service quality impact students' purchasing decisions at modern coffee shops in Malang. Modern coffee shops are increasingly in demand by students who make this place not only as a location to enjoy coffee drinks, but also as a place to gather to work on their college assignments. Many things are considered by consumers in purchasing decisions, including lifestyle, price and service quality. This research involves explaining phenomena through a quantitative method. A survey was distributed through Google Form to gather data from 100 participants. Findings suggest that lifestyle has no significant impact on purchasing choices, unlike price and quality of service. Lifestyle, price, and service quality together influence buying decisions.